Improved FBX chemical dosimeter system with enhanced radiochemical yield for reference dosimetry in radiobiology and radiotherapy research. (September 2020) - Polanek, R.; Varga, Z.; Fodor, E.; Brunner, Sz.; Szabó, E.R.; Tőkés, T.; Hideghéty, K.
Abstract: Radiation dosimetry plays important role in the reproducibility of radiobiology experiments, in the replicability of results, as well as in the successful and safe use of radiotherapy procedures. The consistency and accuracy of the applied dosimetry methods pre-define the outcomes of these applications. This paper presents a version of the well-known ferrous sulphate – benzoic acid – xylenol orange (FBX) chemical dosimeter with improved sensitivity, accuracy and precision. Sensitivity is increased due to a slight modification in composition and the preparation procedures. We use stock solutions for the preparation of the dosimeter solution, which consists of 1 mM ferrous sulphate and 16 mM benzoic acid with 0.25 mM xylenol orange added post-irradiation. The nonlinear response to the absorbed dose of this system is eliminated by the increased ferrous sulphate concentration, permitting the calculation of the absorbed dose by a linear relationship between the absorbed dose and the optical absorbance of the solution. The measured chemical yield of our dosimeter is 9.08 ⋅ 10 − 6 m o l / J for 6 MV photon beams and 6.42 ⋅ 10 − 6 m o l / J for 250 kVp x-rays. This is a 24% enhancement over the original FBX solution, which permits a finer dose resolution. The accuracy and precision of our method is assured by a well-designed and consistently used practice. A custom designed multipurpose PMMA slab phantom was used for irradiation in reference conditions. This phantom can be used for irradiation in reference conditions of dosimetric solutions, dosimetric films and chemical or biological samples. The combined standard uncertainty of this system is 1.12%, which can be improved by using an appropriate temperature correction factor. Furthermore, a working protocol has been established which allows dosimetry measurements using less than 1 mL dosimetric solutions. Highlights: The sensibility of FBX dosimeter was improved by modifying its composition. A special, multipurpose PMMA phantom was constructed for reference irradiation. Chemical and biological samples can be irradiated using different sample holders. The combined standard uncertainty of the system is 1.12%. Further improvements can be made considering the influence of temperature.